The Orthopedic Consult Survival Guide - Hodax, Jonathan D.; Eltorai, Adam E. M.; Daniels, Alan H. (Springer International Publishing : Imprint: Springer, 2017)
This is a quick-reference resource covering the most common acute orthopedic injuries. Including bulleted text and easy-to-follow algorithms, protocols, and images, this "pocket consultant" provides the most up-to-date information when you need it most. Organized anatomically for fast reference, each chapter is broken down into the most common and most serious injuries with tips on how to evaluate and treat adult and pediatric patients. Each injury pattern discussed includes a brief description covering what to ask, what to bring, what to request, what to test, what to look for, and how to further evaluate. The contributing authors are senior orthopedic surgery residents at a major Level-1 Trauma Center who have experience managing a high volume of orthopedic injuries and who have trained many young residents. Covering all aspects of acute care, The Orthopedic Consult Survival Guide is an indispensable tool for medical students, residents, fellows, attendings , and affiliated providers in orthopedic surgery, emergency medicine, and surgery caring for orthopedic patients in emergency rooms, urgent care centers, and primary practice settings.
Keywords: Medicine.; Emergency medicine.; Orthopedics.; Sports medicine.; elektronické knihy; electronic books